EFEITO DA ANESTESIA TÓPICA NÃO-INVASIVA NO CONTROLE DA DOR E ANSIEDADE DURANTE O TRATAMENTO PERIODONTAL EM PORTADORES DE NECESSIDADES ESPECIAIS - Wambier, Letícia Maíra (2014)
This study evaluated the effect of a thermosensitive liposomal anesthetic gel on pain and anxiety during nonsurgical periodontal treatment in patients with special needs. Material and Methods: This study was designed as a split mouth randomized bind clinical trial. Thirty-two young subjects (17.4 ± 5.6) of both genders were selected according to the inclusion criteria: moderate intellectual disability, minimum of 16 teeth, at least one tooth in each sextant with probing depth ≥ 4 mm. Prior periodontal treatment, the index of plaque, marginal bleeding, probing pocket depth and bleeding were obtained. The experimental gel tested was composed of 5% prilocaine/lidocaine, microemulsion thermosensitive liposomal phospholipid gel. It was compared to a commercially available gel Oraqix (5% prilocaine/lidocaine-thermosensitive gel).The negative controls for both gels were periodontal treatment without anesthesia and the rescue drug used was EMLA cream (5% prilocaine/lidocaine), applied in the periodontal pocket if there was discomfort during scaling and root planning (SRP). The parameters used to assess pain intensity and dental anxiety during periodontal treatment were: Hannallah pain scale; Wong-Baker faces pain rating scale and 11-point numerical rating scale, blood pressure and oxygen saturation. All data were compared with ANOVA and chi-square tests. Results: Hannallah pain scale showed significant difference (p<0.05) during SRP. Wong-Baker faces pain rating scale and 11-point numerical rating scale, blood pressure and oxygen saturation did not have significant difference among groups (p>0.05). The anesthetic gel preference between male and female showed significant difference (p<0.0001). Conclusion: Most of the handicapped patients did not require anesthesia to control pain and anxiety during non-surgical periodontal treatment (SRP). Therefore, the non-invasive topical anesthesia could be indicated for anxious patients.